Interception of weevils on cut flowers from South Africa by Korea plant quarantine - Wonhoon Lee; Jung-Hoon Hwang; Jong-Ho Lee; Ki-Jeong Hong (Journal of Asia-Pacific Biodiversity, 2017)
In 2015, a total of 31 samples belonging to superfamily Curculionoidea (Coleoptera) were intercepted from the cut flowers imported from South Africa at the Korean quarantine border. These samples were identified based on the available literature, and they were confirmed as 11 species belonging to four families. However, only three species were identified at the species level. The others were only classified into seven genera and one tribe level. Until now, there have been very few studies about weevils distributed in Africa. Consequently, there is a lack of available information for species identification of intercepted weevils at the quarantine border. This study aims to raise public awareness regarding the introduction of unwanted insect pests from the international trade of plants and/or plant products. It also suggests the need for international cooperation and taxonomic networking for the identification of intercepted pests. Keywords: Curculionoidea, cut flower, interception, plant quarantine, taxonomic networking system